2016
DOI: 10.1590/s0080-623420160000200020
|View full text |Cite
|
Sign up to set email alerts
|

Nursing care for women with pre-eclampsia and/or eclampsia: integrative review

Abstract: Objective: To analyze the available evidence in the literature on nursing care for women with pre-eclampsia and/or eclampsia. Methods: Integrative review searching for primary studies in the databases PubMed, CINAHL, LILACS and SciELO. Results: The sample size consisted of 17 primary studies published between January 2000 and December 2014, grouped into four categories: standardizing blood pressure measurement technique; training with simulation; instruments for standardization of care and quality of care The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
26

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 27 publications
0
11
0
26
Order By: Relevance
“…In the literature, it is reported that the use of magnesium sulfate combined with quality care decreases mortality by 50% in pre-eclampsia and eclampsia. 18 It is described that, in the conception of nursing care for pregnant women with SHEG, monitoring of urinary output and respiratory rate, maintenance of pressure curves, and surveillance of fetal vitality through heart rate auscultation consist of positive interventions and valuable for the achievement of quality of care .6,7,10 Thus, the quality of care for pregnant women with pre-eclampsia and eclampsia was reduced by 50% with the risk of mortality. 18 It is also noted that execution of nursing care based on connected and dynamic actions implies the adoption of a certain technical model based on a scientific method for the solution of problems and needs fulfillment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, it is reported that the use of magnesium sulfate combined with quality care decreases mortality by 50% in pre-eclampsia and eclampsia. 18 It is described that, in the conception of nursing care for pregnant women with SHEG, monitoring of urinary output and respiratory rate, maintenance of pressure curves, and surveillance of fetal vitality through heart rate auscultation consist of positive interventions and valuable for the achievement of quality of care .6,7,10 Thus, the quality of care for pregnant women with pre-eclampsia and eclampsia was reduced by 50% with the risk of mortality. 18 It is also noted that execution of nursing care based on connected and dynamic actions implies the adoption of a certain technical model based on a scientific method for the solution of problems and needs fulfillment.…”
Section: Resultsmentioning
confidence: 99%
“…18 It is described that, in the conception of nursing care for pregnant women with SHEG, monitoring of urinary output and respiratory rate, maintenance of pressure curves, and surveillance of fetal vitality through heart rate auscultation consist of positive interventions and valuable for the achievement of quality of care .6,7,10 Thus, the quality of care for pregnant women with pre-eclampsia and eclampsia was reduced by 50% with the risk of mortality. 18 It is also noted that execution of nursing care based on connected and dynamic actions implies the adoption of a certain technical model based on a scientific method for the solution of problems and needs fulfillment. 19 It reflects, at this first moment, from the perspective of the Organizational or Systemic Principle, which emphasizes the vision in which the whole is more than the union of the parts being interconnected and having recent qualitative phenomena denominated emergencias as organizational effects of the parts in the systemic unit.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6] For data analysis, the selected items of the instrument mentioned were title; journal; authors; instrument; main results or orientations of the authors, also adding specific items of the research theme, such as translation protocol, country and sign language. Most of the instruments used were focused on mental health, covering aspects such as quality of life and self-esteem, and one scale was intended to measure intimacy between spouses.…”
Section: Methodsmentioning
confidence: 99%
“…Contribuindo na prevenção de complicações e redução das taxas de morbimortalidade. Pois o cuidado clínico pode auxiliar em diversas situações, como: na identificação precoce de sinais de préeclâmpsia, no exame físico criterioso, no acompanhamento crítico de exames laboratoriais, na avaliação fetal, na capacitação dos profissionais e na construção de espaço de diálogo 9 .…”
Section: Introductionunclassified